Characteristics of marine shipping emissions at berth: profiles for particulate matter and volatile organic compounds - Q. Xiao; Q. Xiao; Q. Xiao; M. Li; M. Li; M. Li; H. Liu; H. Liu; M. Fu; M. Fu; M. Fu; F. Deng; et al. (Atmospheric Chemistry and Physics, 2018)
Emissions from ships at berth play an important role regarding the exposure of high density human populations to atmospheric pollutants in port areas; however, these emissions are not well understood. In this study, volatile organic compounds (VOCs) and particle emissions from 20 container ships at berth were sampled and analyzed during the <q>fuel switch</q> period at Jingtang Port in Hebei Province, China. VOCs and particles were analyzed using a gas chromatography-mass spectrometer (GC-MS) and a single particle aerosol mass spectrometer (SPAMS), respectively. VOC analysis showed that alkanes and aromatics, especially benzene, toluene and heavier compounds e.g., n-heptane, n-octane and n-nonane, dominated the total identified species. Secondary organic aerosol (SOA) yields and ozone (O3) forming potential were 0.017 ± 0.007 g SOA g−1 VOCs and 2.63 ± 0.37 g O3 g−1 VOCs, respectively. Both positive and negative ion mass spectra from individual ships were derived and the intensity of specific ions were quantified. Results showed that elemental carbon (35.74 %), elemental carbon–organic carbon mixtures (33.95 %) and Na-rich particles (21.12 %) were major classes, comprising 90.7 % of the particles observed. Particles from ship auxiliary engines were in the 0.2 to 2.5 µm size range, with a peak occurring at around 0.4 µm. The issue of using vanadium (V) as tracer element was examined, and it was found that V was not a proper tracer of ship emissions when using low sulfur content diesel oil. The average percentage of sulfate particles observed in shipping emissions before and after switching to marine diesel oil remained unchanged at 24 %. Under certain wind conditions, when berths were upwind of emission sources, the ratios before and after 1 January were 35 and 27 % respectively. The impact of atmospheric stability was discussed based on PM2.5 and primary pollutant (carbon monoxide) concentration. With a background of frequent haze episodes and complex mechanisms of particulate accumulation and secondary formation, the impact of atmospheric stability is believed to have been weak on the sulfate contribution from shipping emissions. The results from this study provide robust support for port area air quality assessment and source apportionment.